The Grouping-Induced Numerosity Illusion Is Attention-Dependent - Pomè, Antonella; Caponi, Camilla; Burr, David C. (Frontiers in Human Neuroscience, 2021)
Perceptual grouping and visual attention are two mechanisms that help to segregate visual input into meaningful objects. Here we report how perceptual grouping, which affects perceived numerosity, is reduced when visual attention is engaged in a concurrent visual task. We asked participants to judge the numerosity of clouds of dot-pairs connected by thin lines, known to cause underestimation of numerosity, while simultaneously performing a color conjunction task. Diverting attention to the concomitant visual distractor significantly reduced the grouping-induced numerosity biases. Moreover, while the magnitude of the illusion under free viewing covaried strongly with AQ-defined autistic traits, under conditions of divided attention the relationship was much reduced. These results suggest that divided attention modulates perceptual grouping of elements by connectedness and that it is independent of the perceptual style of participants.